Pedagogical Significance and Educational Aspects of Teaching Mother Tongue Science - Alimova Dildora Mamatqulovna (Scientific Trends, 2023)
Today's pedagogy, in focusing on the native language, requires responsibility for the educator. In each student it is necessary to teach that the writing technique is expressed through sound and clapping. In the process of pure language tone and spelling of each elat and nation, the responsibility of developing educational aspects of the participating reader is important.
Keywords: native language, education, knowledge, methodology, students, skills, phonetics, Foundation, capacity, importance, knowledge.